Refusing to Be Dim in the Digital Era: Revitalizing Bonding and Bridging Social Capital Through Kite Games in Lampung - Rahmadani, Chintia Eka; Karsiwan (Asketik: Jurnal Agama dan Perubahan Sosial, 2026)
This study aims to examine the social values contained in the traditional kite game in Lampung using the framework of Robert D. Putnam's social capital theory. Kite games not only serve as folk entertainment, but also as a means of building social character, strengthening solidarity, and preserving local culture. Through a qualitative approach with phenomenological methods and case studies, this study explores the experiences, interactions, and meanings that emerge in the practice of making, flying, and kite racing. The results of the study show that this game contains the values of cooperation, sportsmanship, skills, creativity, and social harmony that are internalized in people's lives. In addition, the kite tradition acts as a medium of expression of Lampung's cultural identity, as well as building social capital bonds through internal community ties and bridging social capital through cross-generational and inter-village interactions. In the midst of the challenges of digitalization, kite games remain relevant as a space for social learning, a means of cultural revitalization, and a forum for the formation of new social networks. Thus, the traditional game of kite can be seen as a cultural practice that contributes to strengthening social capital and community cohesion in the contemporary era.